Twenty years of development - International Center for Research on Women (ICRW, 1996)
Women in development: multi-sectoral perspectives--Employment--Sexuality and HIV/AIDS--Family Planning--Nutrition--Environment and natural resources--Leadership and human rights--Fellows program--Outreach and dissemination.